The Mediating Role of Emotion Dysregulation in the Relation Between Adult Attachment Insecurity and Depression Among Young Gay and Bisexual Men. Issue 2 (3rd April 2019) - Wood, Erica P.; Cook, Stephanie H.; Calebs, Benjamin J.
Abstract: Objectives: Attachment insecurity may be more pronounced among young gay and bisexual men (YGBM). Further, attachment insecurity is associated with dysregulated patterns of emotion regulation, which can lead to depression. However, pathways linking attachment insecurity to depression are underexplored among YGBM. Methods: This study used pilot data from N = 67 YGBM to examine if emotion dysregulation mediated the association between attachment insecurity and depression. Results: Results supported the study hypotheses. Attachment insecurity was associated with emotion dysregulation, which was associated with depression. Conclusion: Findings provide preliminary evidence that emotion regulation training may be a useful approach for addressing depression among YGBM.